Comparison of intramedullary nailing fixation and percutaneous locked plating fixation for the treatment of proximal tibial fractures: A meta-analysis. (6th July 2021) - Ren, Cheng; Li, Ming; Sun, Liang; Li, Zhong; Xu, Yibo; Lu, Yao; Wang, Qian; Ma, Teng; Xue, Hanzhong; Zhang, Kun
Objective: This meta-analysis aimed to systematically compare the clinical outcomes of intramedullary nailing (IMN) fixation and percutaneous locked plating (PLP) fixation in the treatment of proximal tibial fractures. Methods: We searched PubMed, Embase, Cochrane library, China National Knowledge Infrastructure (CNKI), China Science and Technology Journal Database (VIP), and Wan Fang to select relevant articles up to March 29, 2020 without language limit. Continuous variables were estimated by weighted mean difference (WMD) with a 95% confidence interval (CI) and dichotomous outcomes were calculated by relative risk (RR) with 95% CI. Moreover, heterogeneity analysis was evaluated. Furthermore, publication bias assessment and sensitivity analysis were conducted. Stata 11.0 software was used to perform the statistical analysis. Results: Ten studies involving 667 cases (321 from IMN fixation group and 346 from PLP fixation group) were included. The type of fractures involved in the included articles was extra-articular proximal tibia fractures. IMN fixation method achieved significantly shorter union time ( WMD = −2.88, 95% CI : −3.23 to −2.53, p < 0.001) and full weight-bearing time ( WMD = −2.81, 95% CI : −3.64 to −1.97, p < 0.001) than PLP fixation method. Meanwhile, IMN fixation resulted in lower risks of infection ( RR = 0.50, 95% CI : 0.27 to 0.91, p = 0.02) and total complications ( RR = 0.36, 95% CI : 0.22 to 0.60, p < 0.001) than PLP fixation. No significant differences were found in the incidence of nonunion ( p = 0.33), malunion ( p = 0.38), and osteofascial compartment syndrome (OCS, p = 0.62) between the two groups. Conclusions: Compared to PLP fixation, IMN fixation had several advantages in treating proximal tibial fractures, including the short time of union and full weight-bearing, as well as a low risk of infection and total complications.